Effect of Demographic Factors on Consumers#x2019; Perception of Online Shopping (Global Journal of Management and Business Research, 2018)
The growing use of internet in India especially in urban area provides an ideal platform for online shopping. The e-marketer can identify the various factors which affects buying behaviour of on line shoppers which can be used to develop marketing strategies. This will help not only in retaining existing customers but also converting potential customers into active one. The objective of the present study was to understand the consumers perception of online shopping and factors affecting it. To understand the perception of buyers, a survey was conducted using the structured questionnaire. The primary data was obtained from 100 respondents who have been using the online shopping. The data was analysed using SPSS software. ANOVA was used to find if there is any significant difference in the perception of respondents on the basis of demographic factors. It has been found that gender, age and annual income of respondents does not influence the customer perception where as educational qualification, marital status has significant impact in adoption of online shopping.
Keywords: consumer perception; online shopping; ecommerce; demographic factors